2016
DOI: 10.1017/s136898001600207x
|View full text |Cite
|
Sign up to set email alerts
|

Latino parents’ perceptions of the eating and physical activity experiences of their pre-school children at home and at family child-care homes: a qualitative study

Abstract: Objective: Research indicates that healthful eating and physical activity (PA) practices implemented in child-care settings can have a positive effect on children's healthful behaviours in this setting, and this effect on healthful behaviours may possibly transfer to the home environment. While more research is needed to examine whether behaviours learned in family child-care homes (FCCH) transfer, the potential for transferability is especially important given that Latino children's home environment has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 32 publications
3
29
0
Order By: Relevance
“…These findings are consistent with those of Lindsay et al. 29 whereby Latino parents also reported that foods served in FCCHs were more healthful than the foods served at home, and trusted FCCPs serve healthy foods to their children. Parents that did inquire about foods served to children at the FCCH found the information provided beneficial.…”
Section: Domain Ii: Awareness Of the Fcch Nutrition And Food Environmentsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings are consistent with those of Lindsay et al. 29 whereby Latino parents also reported that foods served in FCCHs were more healthful than the foods served at home, and trusted FCCPs serve healthy foods to their children. Parents that did inquire about foods served to children at the FCCH found the information provided beneficial.…”
Section: Domain Ii: Awareness Of the Fcch Nutrition And Food Environmentsupporting
confidence: 90%
“…It was evident that daily routines were primarily influenced by parents' work schedules, which can interfere with a parents' ability to create and maintain healthy environments. 29,43 Identifying strategies that are perceived by parents as less burdensome, may encourage parents to seek child nutrition information from their FCCP. Federal nutrition programs like the Child and Adult Care Food Program (CACFP) provide free child nutrition education resources for child care providers who participate in the program.…”
Section: Domain Ii: Awareness Of the Fcch Nutrition And Food Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Family childcare is home‐based, and providers care for children other than their own in the providers' own home. Family childcare may be licensed or unlicensed, and despite the growing interest in this type of setting, further exploration of PA and sedentary in family childcare settings is needed because available studies show that PA levels have been low among preschool‐age children attending licensed family childcare homes (Lindsay et al., ; Vanderloo, Martynuik, & Tucker, ). Home‐based care provided by a nanny or a babysitter often involves childcare hired on a scheduled full‐ or part‐time basis, with care often provided in the child's home.…”
Section: Resultsmentioning
confidence: 99%
“… 9 Latino parents who enrol their children in an FCCH believe that these settings are instrumental in shaping and reinforcing their children’s healthy eating and physical activity habits. 10 11 In fact, recent research suggests that FCCH providers may be more influential than, or equally as important as, parents in shaping food preferences of young children. 5 12 FCCH providers, like parents, help establish and reinforce early healthy eating and physical activity behaviours among young children by developing an environment that fosters healthy behaviours.…”
Section: Introductionmentioning
confidence: 99%